2001
DOI: 10.1016/s1010-7940(01)00718-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of pleural lavage cytology after resection for non-small cell lung cancer

Abstract: The cytologic results of lavage were positive for malignant cells in eight of 85 patients (9.4%). The existence of cancer cells in the pleural cavity can be the result of their exfoliation or surgical manipulations. The mechanical irrigation subdivides the percentage of positive samples. Our study supports that the positive findings on pleural lavage cytology is an essential prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Positive cytology has been found to be more frequently associated with adenocarcinomas, N2 disease, stage III tumors, in tumors in which there is visceral pleural involvement, in the presence of lymphatic permeation, or vascular invasion. It has invariably been associated with increased recurrence and a worse prognosis [47][48][49][50][51][52]. It is unlikely that one can achieve complete resection in tumors in which pleural lavage cytology is positive.…”
Section: Pleural Lavage Cytologymentioning
confidence: 99%
“…Positive cytology has been found to be more frequently associated with adenocarcinomas, N2 disease, stage III tumors, in tumors in which there is visceral pleural involvement, in the presence of lymphatic permeation, or vascular invasion. It has invariably been associated with increased recurrence and a worse prognosis [47][48][49][50][51][52]. It is unlikely that one can achieve complete resection in tumors in which pleural lavage cytology is positive.…”
Section: Pleural Lavage Cytologymentioning
confidence: 99%
“…It was found that 90% of the cases that underwent bilobectomy had tumors with irregular edge. Many scholars argue that exfoliation of tumor cells from metastatic lymph nodes into pleural cavity after surgical manipulations lead to positive cytology after lung resection [23,24]. Although the reason for positive cytology is not yet fully known, we do not think that this theory is completely valid.…”
Section: Discussionmentioning
confidence: 88%
“…Although the prognosis of patients who have primary lung cancer with positive PLC is poor [1][2][3][4], there have been no new therapeutic methods to alleviate these patients' condition. Recently, Ichinose et al [8] reported a prematurely trial of intrapleural hypotonic cisplatin treatment for PLC positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of patients who have primary lung cancer with positive pleural lavage cytology (PLC) is poor compared to that of other patients who have lung cancer in the same histological stage, but are PLC negative [1][2][3][4]. Some investigators have insisted that we should treat patients with positive PLC the same as patients with malignant pleural effusions that are pathologically categorized to stage IIIB [5,6].…”
Section: Introductionmentioning
confidence: 99%